2017
DOI: 10.1016/j.jhazmat.2016.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polypropylene glycols and polyethylene glycol carboxylates in flowback and produced water from hydraulic fracturing

Abstract: The purpose of the study was to separate and identify the unknown surfactants present in flowback and produced water from oil and gas wells in the Denver-Julesburg Basin (Niobrara Formation) in Weld County, Colorado, USA. Weld County has been drilled extensively during the last five years for oil and gas between 7000-8000 feet below land-surface. Polypropylene glycols (PPGs) and polyethylene glycols carboxylates (PEG-Cs) were found for the first time in these flowback and produced water samples. These ethoxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 17 publications
3
51
0
1
Order By: Relevance
“…Among these, a series of polyethylene glycol (PEGs, H-(OC2H4)n-OH) surfactants were detected (Fig. 2A, shaded region), consistent with the chemicals previously reported by Thurman et al (2016) in HF-FPW samples from the United States. The PEG surfactants are polymers of ethylene oxide (EO) units, and those identified here included PEG-EO4 to PEG-EO13 (i.e.…”
Section: Untargeted Trace Organics Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Among these, a series of polyethylene glycol (PEGs, H-(OC2H4)n-OH) surfactants were detected (Fig. 2A, shaded region), consistent with the chemicals previously reported by Thurman et al (2016) in HF-FPW samples from the United States. The PEG surfactants are polymers of ethylene oxide (EO) units, and those identified here included PEG-EO4 to PEG-EO13 (i.e.…”
Section: Untargeted Trace Organics Analysissupporting
confidence: 89%
“…The PEG surfactants are polymers of ethylene oxide (EO) units, and those identified here included PEG-EO4 to PEG-EO13 (i.e. n = 4-13), also similar to the results of Thurman et al (2016). Here all the PEG-EOn species were confirmed by accurate masses of the protonated or ammonium adducted ions, as well as by diagnostic fragmentation in MS/MS experiments.…”
Section: Untargeted Trace Organics Analysissupporting
confidence: 78%
“…While this literature review identified 1,198 chemicals in produced water with CAS numbers, there are additional constituents of potential concern, such as isomers or homologous series of various compounds ( Thurman et al, 2017 ), which cannot be represented by a single CAS number, and therefore were not included in this study. For the purposes of this study, requiring a CAS number allowed for rapid cross-reference to numerous other databases and facilitated identification of associated data.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the compounds associated with either hydraulic fracturing fluids or those identified in produced water lack established analytical methods ( Oetjen et al, 2017 ; U.S. EPA, 2018 ). Advanced research-based analytical methods have been used to detect and quantify organic compounds in produced water, including homologous series of surfactants ( Nell and Helbling, 2018 ; Thurman et al, 2017 , 2014 ), biocides ( Nell and Helbling, 2018 ), and compounds that are suspected additives but which are unreported to FracFocus ( Hoelzer et al, 2016 ; Sitterley et al, 2018 ). Overall, there is not a comprehensive understanding of produced water composition ( Ferrer and Thurman, 2015 ; Nell and Helbling, 2018 ; Oetjen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Filtration and centrifugation are other kinds of separation for virtually eliminating the particulate components to deal more compatibility with the analytical methodologies. Moreover, filtration processes would not have the ability of dissolved fractional component alteration (Ferrer and Thurman 2015;Mitra 2004;Oetjen et al 2017Oetjen et al , 2018Rodriguez-Aller et al 2016;Thurman et al 2017).…”
Section: Treatment Challengesmentioning
confidence: 99%